2019
DOI: 10.3389/fpls.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Puroindoline a in Durum Wheat Affects Milling and Pasting Properties

Abstract: Durum wheat has limited culinary utilizations partly due to its extremely hard kernel texture. Previously, we developed transgenic durum wheat lines with expression of the wildtype Puroindoline a ( Pina ) and characterized PINA’s effects on kernel hardness, total flour yield and dough mixing properties in durum wheat. The medium-hard kernel texture is potentially useful for exploring culinary applications of durum wheat. In the present study, we examined the millin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Numerous studies have been focused on mining allelic variations and the genotype-phenotype association of Pin, resulting in the identification of 26 alleles of Pina, 33 alleles of Pinb and a few double null alleles [21,22,[77][78][79][80][81][82][83][84][85][86][87]. Manipulation of the expression or genotypes of Pin not only modifies kernel hardness and milling properties in common and durum wheat lines [62][63][64]67,[88][89][90][91][92], but also changes some parameters of the end-use quality and storage protein interaction [29,[93][94][95]. Owing to its importance, research regarding Pin has been comprehensively reviewed by Bhave et al [21,22] in aspects of its genetics, polymorphism identification and studies about its biological functions.…”
Section: Pins Are the Major Causal Genes For Wheat Kernel Hardnessmentioning
confidence: 99%
“…Numerous studies have been focused on mining allelic variations and the genotype-phenotype association of Pin, resulting in the identification of 26 alleles of Pina, 33 alleles of Pinb and a few double null alleles [21,22,[77][78][79][80][81][82][83][84][85][86][87]. Manipulation of the expression or genotypes of Pin not only modifies kernel hardness and milling properties in common and durum wheat lines [62][63][64]67,[88][89][90][91][92], but also changes some parameters of the end-use quality and storage protein interaction [29,[93][94][95]. Owing to its importance, research regarding Pin has been comprehensively reviewed by Bhave et al [21,22] in aspects of its genetics, polymorphism identification and studies about its biological functions.…”
Section: Pins Are the Major Causal Genes For Wheat Kernel Hardnessmentioning
confidence: 99%
“…Manipulation of the level of grain hardness not only modifies milling properties in common and durum wheat lines ( Li et al., 2014 ; Wang et al., 2019a ), but also changes some parameters of the end-use quality and storage protein interaction ( Kiszonas and Morris, 2018 ; Wang et al., 2019b ). The previous studies reported that Pin genes could only explain over 60% of the trait’s variation and hinder the identification of other QTLs with minor effects in the bi-parental mapping population ( Sourdille et al., 1996 ; Campbell et al., 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown, wheat puroindolines PIN-a and PIN-b play an important role in the grain texture and are markers available to improve wheat hardness in breeding programs [ 126 ]. The expression of both Pina and Pinb genes, encoding puroindolines PIN-a and PIN-b, is necessary for the soft-kernel phenotype, whereas deletion or loss-of-function mutations in any of these genes lead to hard endosperms [ 127 ]. The presence of starch-bound PIN-a and PIN-b (friabilin) rather than total PINs’ content affects the hardness of wheat grains [ 128 ].…”
Section: Possible Applications Of Plant Lipid-binding Proteinsmentioning
confidence: 99%